Optimization of Laccase Adsorption-Desorption Behaviors on Multi-Walled Carbon Nanotubes for Enzymatic Biocathodes - Suherman, Alex Lukmanto; Zebda, Abdelkader; Martin, Donald K. (UI Scholars Hub, 2018)
Laccase adsorption-desorption behaviors on the surface of multi-walled carbon nanotubes (MWCNTs) were investi-gated using spectrophotometry and voltammetry. The optimum condition for laccase adsorption is 5.0 mg/mL of laccase in 0.01 M phosphate-buffered saline (PBS) at pH 5.0. Laccase adsorption is a reversible phenomenon that is dependent upon the nature of MWCNTs and the concentration of ionic strength in the laccase solution. Chitosan was functiona-lized as a nanoporous reservoir to minimize laccase desorption. Chitosan was found to protect approximately 97.2% of the adsorbed laccase from MWCNTs during the first six hours of observation. The three-dimensional (3D) biocathode, MWCNTs-laccase-chitosan with a 0.2 cm2 geometric area, was shown to have a stable open circuit potential (OCP) of 0.55 V, a current density of 0.33 mA cm-2 at 0.2 V vs. saturated calomel electrode (SCE), and a stable current for 20 hours of successive measurements. This report provides a new insight into the study of a high-performance laccase-based biocathode via optimization of adsorption and minimization of desorption phenomena.